2019
DOI: 10.1177/2396987319889258
|View full text |Cite
|
Sign up to set email alerts
|

Early in-hospital exposure to statins and outcome after intracerebral haemorrhage – Results from the Virtual International Stroke Trials Archive

Abstract: Introduction: Recent data suggest that statin use after intracerebral haemorrhage might be beneficial. However, data on the effects of early in-hospital statin exposure are lacking. Therefore, we sought to assess whether (1) early statin exposure during the acute phase after intracerebral haemorrhage and (2) early continuation of prevalent statin use are associated with favourable functional outcome. Patients and methods: Data were obtained from the Virtual International Stroke Trials Archive. Patients were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…62 Targeting ICH mechanisms using combination therapy on patients that can be accrued on an adaptive trial design may also result in better therapeutic combined stratified strategies and algorithms than targeting single mechanisms individually (Figure 4) and less investigator bias with proper statistical Bayesian implementation. 26 Knowledge of various mechanisms of ICH as delineated in this review have increased over the last decade. Adaptive trial design will allow for the optimization of the various mechanisms that have shown promise in the last few decades but have not been able to produce a definitive Phase 3 trial demonstrating improved outcome.…”
Section: Adaptive Trial Design and Combination Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…62 Targeting ICH mechanisms using combination therapy on patients that can be accrued on an adaptive trial design may also result in better therapeutic combined stratified strategies and algorithms than targeting single mechanisms individually (Figure 4) and less investigator bias with proper statistical Bayesian implementation. 26 Knowledge of various mechanisms of ICH as delineated in this review have increased over the last decade. Adaptive trial design will allow for the optimization of the various mechanisms that have shown promise in the last few decades but have not been able to produce a definitive Phase 3 trial demonstrating improved outcome.…”
Section: Adaptive Trial Design and Combination Therapymentioning
confidence: 99%
“… 3 , 14 Calcium influences physiological homeostasis by playing a critical role in the coagulation cascade and neuronal, skeletal, smooth muscle, and hormone secretion. 26 28 Serum calcium is normally found ionized and charged (active physiological form), in a free state and protein bound, or as an anion bound complex. 14 , 15 Calcium is regulated by parathyroid hormone, vitamin D metabolites, and calcitonin.…”
Section: Acute Intervention Targets For Attenuating Secondary Injury After Ichmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these meta-analyses reported a significant decrease in all-cause mortality and all-stroke types [ 11 - 12 ]. Several retrospective studies showed promising mortality and functional outcomes with an early continuation of statin therapy and poor outcomes in post-ICH patients who discontinued statins [ 13 - 14 ]. According to several meta-analyses, statin use in ICH patients is linked to better functional outcomes and reduced mortality, which suggests that patients who start taking statins or continue taking them after admission are more likely to have positive clinical results [ 15 - 16 ].…”
Section: Introductionmentioning
confidence: 99%